Commensal bacterial sharing does not predict host social associations in kangaroos. Issue 11 (29th July 2019) - Proboste, Tatiana; Corvalan, Paloma; Clark, Nicholas; Beyer, Hawthorne L.; Goldizen, Anne W.; Seddon, Jennifer M.
Abstract: Social network analysis has been postulated as a tool to study potential pathogen transmission in wildlife but is resource‐intensive to quantify. Networks based on bacterial genotypes have been proposed as a cost‐effective method for estimating social or transmission network based on the assumption that individuals in close contact will share commensal bacteria. However, the use of network analysis to study wild populations requires critical evaluation of the assumptions and parameters these models are founded on. We test (a) whether networks of commensal bacterial sharing are related to hosts' social associations and hence could act as a proxy for estimating transmission networks, (b) how the parameters chosen to define host associations and delineate bacterial genotypes impact inference and (c) whether these relationships change across time. We use stochastic simulations to evaluate how uncertainty in parameter choice affects network structure. We focused on a well‐studied population of eastern grey kangaroos ( Macropus giganteus), from Sundown National Park, Australia. Using natural markings, each individual was identified and its associations with other kangaroos recorded through direct field observations over 2 years to construct social networks. Faecal samples were collected, Escherichia coli was cultured and genotyped using BOX‐PCR, and bacterial networks were constructed. Two individuals were connected in the bacterial network if they shared at least one E. coli genotype. We determined the capacity of bacterial networks to predict the observed social network structure in each year. We found little support for a relationship between social association and dyadic commensal bacterial similarity. Thresholds to determine host associations and similarity cut‐off values used to define E. coli genotypes had important ramifications for inferring links between individuals. In fact, we found that inferences can show opposite patterns based on the chosen thresholds. Moreover, no similarity in overall bacterial network structure was detected between years. Although empirical disease transmission data are often unavailable in wildlife populations, both bacterial networks and social networks have limitations in representing the mode of transmission of a pathogen. Our results suggest that caution is needed when designing such studies and interpreting results. Abstract : The authors tested if a bacterial network in a wild kangaroo population can be used as a reliable proxy for predicting host social network. Using stochastic simulations, they evaluated how uncertainty in parameter choice affects network structure, and found that inferences can show opposite patterns based on the chosen threshold. Resumen: El análisis de redes sociales se ha postulado como una herramienta para estudiar la potencial transmisión de patógenos en fauna silvestre. Sin embargo, las redes sociales en fauna silvestre son difíciles de cuantificar. Es por esto que las redes basadas en el genotipo bacteriano se han propuesto como un método más rentable para estimar redes sociales o de transmisión, basado en el supuesto de que individuos en contacto cercano compartirán bacterias comensales. Sin embargo, el uso del análisis de redes para estudiar poblaciones silvestres requiere una evaluación crítica de los supuestos y parámetros en los que se basan estos métodos. En este estudio probamos (a) si las redes de bacterias comensales están relacionadas con las redes sociales y por lo tanto podrían actuar como proxy para estimar redes de transmisión. Exploramos (b) cómo los parámetros elegidos, para definir asociaciones entre individuos y delinear genotipos bacterianos, impactan en los resultados. Finalmente, examinamos (c) si estas relaciones cambian con el tiempo. Utilizamos simulaciones estocásticas para evaluar cómo la incertidumbre en la elección de parámetros afecta la estructura de la red. Nuestro estudio se basó en una población de canguros grises ( Macropus giganteus ), del Parque Nacional de Sundown, Australia. Cada individuo fue identificado usando marcas naturales, y sus interacciones con otros canguros se registraron a través de observaciones de campo durante dos años para construir redes sociales. Se recolectaron muestras fecales, se cultivó Escherichia coli, se determinó el genotipo mediante BOX‐PCR y se construyeron las redes bacterianas. El criterio para conectar dos individuos en la red bacteriana, se basa en sí al menos un genotipo de E. coli es compartido entre dos individuos. Determinamos la capacidad de las redes bacterianas para predecir la estructura de las redes sociales observadas en cada año. Encontramos poca evidencia que sustente una relación entre la asociación social y la similitud bacteriana. Los umbrales, que determinan las asociaciones entre individuos en las redes sociales y los valores de corte de similitud para definir los genotipos de E. coli, tuvieron una importante influencia para inferir vínculos entre individuos. De hecho, encontramos que las inferencias pueden mostrar patrones opuestos dependiendo de los umbrales elegidos. Además, no se detectó similitud en la estructura de la red bacteriana general entre los años. Aunque los datos empíricos de transmisión de enfermedades a menudo no están disponibles para poblaciones de vida silvestre, los análisis de redes pueden potencialmente solventar dicho problema. Sin embargo, tanto las redes bacterianas como las redes sociales tienen limitaciones para representar el modo de transmisión de un patógeno. Nuestros resultados sugieren que se necesita tener cautela al diseñar este tipo de estudios e interpretar los resultados.